Possible Effects of IR4.0 on Malaysia’s TN50 - R. Nordin, M.; ., .; ., . (International Journal of Engineering and Technology, 2018)
Malaysia’s development since 1970 has been guided by well formulated national development blueprints starting with the New Economic Policy followed by the National Vision Plan. The next stage of Malaysia’s development will span year 2021-2050 and shall be charted by TN50. The latest blueprint is currently being formulated using the bottom-up approach. The period for TN50 is also the era of IR4.0 where disruptive technologies are driving major changes in business models and sustainability. Malaysia will be strongly affected by these changes. Malaysia has done well so far based on production factors tied to low cost of labour and high level of incentive and subsidies. The next level of Malaysia’s development journey requires higher level factors that are tied to competitive advantages such innovation, entrepreneurships, speed and integrity.  These factors are required to ensure continuous presence of manufacturing and trade activities in Malaysia and allow Malaysia to benefits from developments related to IR4.0.